Health information system in primary health care units of the Central Zone, Tigray, Northern Ethiopia - Letekirstos Gebreegziabher Gebretsadik; Abate Bekele Belachew; Gebregziabher Berihu Gebrekidan; Alemayohu Bayray; Akberet Lemlem; Lewtnesh Berihun Dangew; Haftom Temesgen Abebe (BMC Medical Informatics and Decision Making)
Abstract Background Health information systems require the management of health information through health management information systems and research and knowledge management. In many low-income countries, including Ethiopia, poor data quality and limited use of health information remain major challenges in the health system. Reliable health data quality is essential for evidence-based decision-making and improving quality health service delivery. This study aimed to assess and explore the contextual factors of the quality and utilization of health information in primary health care units in the Central Zone, Tigray, Northern Ethiopia. Methods A facility-based cross-sectional quantitative and qualitative study design was used. A total of seven primary health care units and four district health offices were selected. Data were collected via document review, structured questionnaires and in-depth interviews. A three-month document review was conducted to assess data accuracy via lot quality assurance sampling. Forty-eight health professionals, including Woreda Health Office heads, facility heads, health management information system focal persons, service providers and health extension workers, were interviewed for quantitative analysis. Additionally, 23 key informants with the same roles participated in the qualitative interviews. Descriptive statistics were computed, and thematic analysis was conducted for the qualitative data. Results Four of the seven primary health care units have assigned health management information system personnel, and five of them have necessary equipment for health management information systems. The average lot quality assurance sampling of the primary health care units ranged from 35 to 60%, which falls below the national threshold of 90% data accuracy. In knowing and measuring the dimensions of data quality, the informants described this as a difficult task despite acknowledging its importance. Similarly, the culture of data use for decision making was limited. Conclusion This study revealed that primary health care units in the Central Zone of Tigray face significant challenges in terms of data quality and utilization, primarily due to the limited capacity of service providers, unclear understanding of data quality dimensions and weak data use culture. The average lot quality assurance sampling accuracy rates are below the acceptable level, indicating issues in the data documentation and validation processes. Addressing these gaps through targeted capacity-building, including the integration of HMIS curricula at the university level and system-level improvements such as implementing computerized systems, ensuring accountability and allocating budgets, is needed to strengthen health information systems and enable evidence-based decision-making at all levels of the health system.